Ensaio clínico randomizado duplo cego placebo para estudo da eficácia da L-arginina como protocolo terapêutico coadjuvante no tratamento da anemia falciforme - Eleutério, Renata Mirian Nunes (2019)
Sickle cell anemia (SCA) is the most prevalent monogenic disease in Brazil, characterized by the presence of hemoglobin S (HbS) in homozygosity. In the deoxygenated state, the HbS polymerizes by modifying the morphology and compromising the function of the red blood cells. Intravascular hemolysis promotes the release of free hemoglobin, the formation of free radicals that degrade nitric oxide (NO), and the release of arginase, which consume arginine, the substrate for NO formation, both mechanisms contribute to the reduction of synthesis of this potent vasodilator. The pathophysiology of the disease is characterized by recurrent events of hemolysis and vaso-occlusion crises, as well as a systemic inflammatory process with endothelial damage, increased oxidative stress and procoagulant status, presenting a high rate of comorbidities and mortality. In Brazil, continuous use of hydroxyurea (HU) is recommended for the treatment of AF in order to raise the concentration of fetal hemoglobin (HbF), the main clinical modality of the disease. However, the cytotoxicity of HU coupled with resistance by some patients has contributed to the search for alternatives that aid in the treatment, reducing the adverse effects and improving the quality of life. L-arginine is an amino acid that has no listed adverse effects, being the substrate of NO formation, thus improving microcirculation and reducing primarily endothelial damage. Thus, this study aimed to analyze the efficacy of L-arginine as a therapeutic protocol to support the use of HU in the treatment of patients with SCA. It is a randomized, double-blind, placebo-controlled clinical trial of adult patients of both sexes in continuous use of HU for at least two months at a dose of 500mg mg / kg / day in follow-up in the Blood Center of the State of Ceará (HEMOCE). This study was performed in 50 patients, with 25 receiving HU + L-arginine (500mg / day) and 25 patients receiving HU + placebo. The treatment was in the period of four months, with clinical and laboratory evaluations. Before starting the treatment (M0) and every two months of the same (M2, M4), samples of peripheral blood were collected for the laboratory tests: complete blood count, by automatic method, determination of NO by ELISA, determination of HbF, by HPLC and determination of reticulocytes by bright cresyl blue. Arginase dosage was also performed by specific Arginase Activity Assay Kit at the time before treatment with L-arginine (M0) and four months of treatment (M4). The clinical approach was performed through a medical avaliation from the Hematology Department, to evaluate the clinical evolution and possible adverse reactions. Statistical analysis was performed using the statistical program GraphPad Prism® and SPSS®. The level of statistical significance considered for all analyzes was p <0.05. A total of 52% of the patients belonged to females and 48% to males. The mean age was 28 years. Patients had used UH for at least two months, ranging from two to 108 months (9 years). The mean dose of HU occurred in 1040mg in the placebo group and 1070mg in the study group. The increase in NO levels in the study group (HU + L-arginine) occurred significantly in the fourth month of the clinical trial. The frequency of pain reported by patients also decreased in the study group, demonstrating the potential role of L-arginine as a coadjuvant in the treatment of AF. Other clinical and laboratory data showed no differences between the placebo and study groups, including arginase. The clinical trial demonstrated that there was an increase in NO levels and reduction of pain frequency in patients with AF using arginine in association with HU, demonstrating the possibility of this therapy being inserted in the treatment protocol, requiring further trials with longer duration monitoring.